Lethality by pneumonia and factors associated to death - Sidnei Ferreira; Clemax C. Sant'Anna; Maria de Fatima B.P. March; Marilene Augusta R.C. Santos; Antonio Jose Ledo A. Cunha (Elsevier, 2014)
OBJECTIVE: To describe the case-fatality rate (CFR) and risk factors of death in children with community-acquired acute pneumonia (CAP) in a pediatric university hospital. METHOD: A longitudinal study was developed with prospective data collected from 1996 to 2011. Patients aged 1 month to 12 years were included in the study. Those who left the hospital against medical orders and those transferred to ICU or other units were excluded. Demographic andclinical-etiological characteristics and the initial treatment were studied. Variables associated to death were determined by bivariate and multivariate analysis using logistic regression. RESULTS: A total of 871 patients were selected, of whom 11 were excluded; thus 860 children were included in the study. There were 26 deaths, with a CFR of 3%; in 58.7% of these, penicillin G was the initial treatment. Pneumococcus was the most common pathogen (50.4%). From 1996 to 2000, there were 24 deaths (93%), with a CFR of 5.8% (24/413). From 2001 to 2011, the age group of hospitalized patients was older (p = 0.03), and the number of deaths (p = 0.02) and the percentage of disease severity were lower (p = 0.06). Only disease severity remained associated to death in the multivariate analysis (OR = 3.2; 95%CI: 1.2-8.9; p = 0.02). CONCLUSION: When the 1996-2000 and 2001-2011 periods were compared, a significant reduction in CFR was observed in the latter, as well as a change in the clinical profile of the pediatric in patients at the institute. These findings may be related to the improvement in the socio-economical status of the population. Penicillin use did not influence CFR.